A DFT Calculation of Fluoride-Doped TiO(2) Nanotubes for Detecting SF(6) Decomposition Components - Zhang, Xiaoxing (Sensors (Basel), 2017)
Gas insulated switchgear (GIS) plays an important role in the transmission and distribution of electric energy. Detecting and analyzing the decomposed components of SF(6) is one of the important methods to realize the on-line monitoring of GIS equipment. In this paper, considering the performance limits of intrinsic TiO(2) nanotube gas sensor, the adsorption process of H(2)S, SO(2), SOF(2) and SO(2)F(2) on fluoride-doped TiO(2) crystal plane was simulated by the first-principle method. The adsorption mechanism of these SF(6) decomposition components on fluorine-doped TiO(2) crystal plane was analyzed from a micro perspective. Calculation results indicate that the order of adsorption effect of four SF(6) decomposition components on fluoride-doped TiO(2) crystal plane is H(2)S > SO(2) > SOF(2) > SO(2)F(2). Compared with the adsorption results of intrinsic anatase TiO(2) (101) perfect crystal plane, fluorine doping can obviously enhance the adsorption ability of TiO(2) (101) crystal plane. Fluorine-doped TiO(2) can effectively distinguish and detect the SF(6) decomposition components based on theoretical analysis.